2020
DOI: 10.1186/s12916-020-01709-4
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin and other non-steroidal anti-inflammatory drugs and depression, anxiety, and stress-related disorders following a cancer diagnosis: a nationwide register-based cohort study

Abstract: Background Cancer patients have a highly increased risk of psychiatric disorders following diagnosis, compared with cancer-free individuals. Inflammation is involved in the development of both cancer and psychiatric disorders. The role of non-steroidal anti-inflammatory drugs (NSAIDs) in the subsequent risk of psychiatric disorders after cancer diagnosis is however unknown. Methods We performed a cohort study of all patients diagnosed with a first primary malignancy between July 2006 and December 2013 in Swe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 45 publications
0
22
0
1
Order By: Relevance
“…Compared with those with no use of nonsteroidal anti-inflammatory drugs, the use of aspirin alone was associated with a lower rate of depression, anxiety, and stress-related disorders (HR, 0.88; 95% CI 0.81–0.97). [ 46 ] Bhatt et al [ 47 ] demonstrated in animal studies that aspirin improved depression in sprague-dawleyrats both in combination with dexamethasone and alone. The animals treated with aspirin showed increased sucrose preference, decreased immobility-time in the forced swim test, decreased serum cortisol, and increased brain serotonin levels signifying antidepressant action.…”
Section: Common Cardiovascular Drugs In Depressionmentioning
confidence: 99%
“…Compared with those with no use of nonsteroidal anti-inflammatory drugs, the use of aspirin alone was associated with a lower rate of depression, anxiety, and stress-related disorders (HR, 0.88; 95% CI 0.81–0.97). [ 46 ] Bhatt et al [ 47 ] demonstrated in animal studies that aspirin improved depression in sprague-dawleyrats both in combination with dexamethasone and alone. The animals treated with aspirin showed increased sucrose preference, decreased immobility-time in the forced swim test, decreased serum cortisol, and increased brain serotonin levels signifying antidepressant action.…”
Section: Common Cardiovascular Drugs In Depressionmentioning
confidence: 99%
“…Patients who had medications dispensed with ATC codes B01AC06, B01AC30 and B01AC56 were considered as medicated with lose-dose aspirin (limited to daily dose of 75 or 160 mg). We focused on low-dose aspirin that tends to be used in long term in the present study, because of its potential effect of reducing stress-related outcomes [ 14 , 21 ]. Patients who had medications dispensed with ATC code M01A were considered as medicated with non-aspirin NSAIDs.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study, we demonstrated that aspirin was able to block tumour-induced memory impairment in mouse models of breast cancer, suggesting its potential to combat cancer-related cognitive and mood symptoms [ 12 ]. In humans, aspirin and non-aspirin NSAID use was shown to be associated with decreased risk of depression and depressive symptoms [ 13 ], especially in terms of continued use of low-dose aspirin [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, human studies suggest that using aspirin in the year prior to receiving a cancer diagnosis reduced the risk of developing depression, anxiety and stress‐related disorders in the year following a cancer diagnosis (data were adjusted for sociodemographic factors, co‐morbidities and cancer characteristics). Interestingly, aspirin was more protective than other non‐steroidal anti‐inflammatory drugs (NSAIDs) (Hu et al, 2020). Furthermore, the decrease in hippocampal BDNF mRNA that was observed in CT26‐induced colon carcinoma by Yang et al (2014) was not extended to other tumour models, including 4T07 and 4T1 mammary tumour models (Walker Ii et al, 2017) and NMU‐induced ductal mammary tumours (Pyter et al, 2010).…”
Section: Hippocampusmentioning
confidence: 99%